Bilateral inferior petrosal sinus sampling: Procedural data from a German single-center study - Augustin, Anne Marie; Detomas, Mario; Hartung, Viktor; Thurner, Annette; Tröger, Viola; Deutschbein, Timo; Kickuth, Ralph (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2023)
Purpose To assess radiation exposure and diagnostic performance of bilateral inferior petrosal sinus sampling for the distinction of pituitary and ectopic adrenocorticotropin-dependent Cushingʼs syndrome.Materials and Methods Procedural data of bilateral inferior petrosal sinus procedures were retrospectively evaluated. The analysis included the patients’ clinical and demographic data, procedural radiation exposure, and complication rates, sampling results, clinical course of the patients, and calculation of diagnostic performance data.Results The cases of 46 patients diagnosed with adrenocorticotropin-dependent Cushingʼs syndrome were evaluated. Bilateral inferior petrosal sinus sampling was successfully performed in 97.8 % of the cases. The overall median procedure-related fluoroscopy time was 7.8 min. (range 3.2–36.2 min.), and the median procedural dose area product was 11.9 Gy*cm2 (range 2.1–73.7 Gy*cm2). Radiation doses due to digital subtraction angiography series for visualization of the inferior petrosal sinus were 3.6 Gy*cm2 (range 1.0–18.1 Gy*cm2). Radiation doses due to fluoroscopy had a higher impact on the overall radiation exposure and were significantly influenced by the patients’ habitus. The sensitivity, specificity, and positive and negative predictive values were 84 %, 100 %, 100 %, and 72 % before stimulation with corticotropin-releasing hormone, and 97 %, 100 %, 100 %, and 93 % after stimulation. Concordance between magnetic resonance imaging studies and bilateral inferior petrosal sinus sampling results was only found in 35.6 % of the cases. The periprocedural complication rate was 2.2 %, with one patient experiencing vasovagal syncope during catheterization.Conclusion Bilateral inferior petrosal sinus sampling is a safe procedure with high technical success rates und excellent diagnostic performance. The procedure-related radiation exposure shows large variations and depends on the complexity of cannulation as well as the patients’ habitus. Fluoroscopy accounted for the largest proportion of radiation exposure. Acquisition of digital subtraction angiography series for the verification of correct catheter placement appears justified.Key Points: Citation Format
Keywords: Cushingʼs disease; diagnostic radiology; pituitary; interventional procedures; adenoma; bilateral inferior petrosal sinus sampling